Antidepressant Effect of Crocus sativus Aqueous Extract and its Effect on CREB, BDNF, and VGF Transcript and Protein Levels in Rat Hippocampus - Ghasemi, T.; Abnous, K.; Vahdati, F.; Mehri, S.; Razavi, B. M.; Hosseinzadeh, H. (Drug Research, 2015)
Crocus sativus L., commonly known as saffron, is a perennial stemless herb in Iridaceae family. It has been used in traditional medicine as well as in modern pharmacological studies for variety of conditions including depression. Recent studies have suggested brain-derived neurotrophic factor (BDNF), VGF Neuropeptide, Cyclic-AMP Response Element Binding Protein (CREB) and phospho-CREB (p-CREB) may play roles in depression. In this research the molecular mechanism of antidepressant effect of aqueous extract of saffron and its effect on the levels of BDNF, VGF, CREB and p-CREB in rat hippocampus, were investigated. The aqueous extract of saffron (40, 80 and 160 mg/kg/day) and imipramine 10 mg/kg/day were injected intraperitoneally (i.p.) for 21 days to rats. The FST (forced swimming test) was performed on the days 1st and 21st. The protein expression and transcript levels of BDNF, VGF CREB and phospho-CREB in rat hippocampus, were evaluated using western blot and quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The results of FST showed that saffron reduced the immobility time. The protein levels of BDNF, CREB and p-CREB were significantly increased in saffron treated rats. VGF protein expression was also increased, but not significantly. The transcript levels of BDNF significantly increased. No significant changes in CREB and VGF transcript levels were observed. It was concluded that aqueous extract of saffron has antidepressant effects and the mechanism of its antidepressant effect may be due to increasing the levels of BDNF, VGF, CREB and P-CREB in rat hippocampus.
Keywords: saffron; Crocus sativus; antidepressant; forced swimming test; Western blot; BDNF; VGF; CREB; P-CREB